Mothers' high glycemic levels and the association between periodontitis and low birth weight. Issue 7 (7th February 2022) - Gomes‐Filho, Isaac Suzart; Trindade, Soraya Castro; da Cruz, Simone Seixas; Figueiredo, Ana Claudia Morais Godoy; Hintz, Alexandre Marcelo; Adan, Luis Fernando Fernandes; Cerqueira, Eneida de Moraes Marcílio; Passos‐Soares, Johelle de Santana; Vianna, Maria Isabel Pereira; Coelho, Julita Maria Freitas; Alves, Claúdia Maria Coêlho; Barreto, Maurício Lima; et al.
Abstract: Background: Maternal hyperglycemia, periodontitis, and adverse gestational outcomes are important health problems. The present study investigated the hypothesis that periodontitis and the glycemic level of mothers may have opposing influences on birth weight (BW). This study evaluated the effect of high glycemic levels, albeit within the normal range, on the association between periodontitis and low birth weight (LBW). Methods: A total of 732 women took part in this case‐control study; 172 were mothers of children with LBW <2, 500 g, and 560 were mothers of children with BW ≥2, 500 g. The BW of newborns was obtained from medical records, and information on socioeconomic‐demographic, lifestyle behavior were obtained through interviews. Glycated hemoglobin (HbA1c) levels were evaluated, and full‐mouth periodontal examination was carried out within 7 days postpartum. Hierarchical and logistic regression analysis evaluated the effect of glycemic levels on the association between periodontitis and LBW by subgroups, estimating odds ratios (OR) with 95% confidence intervals (95% CI). Results: In the group with HbA1c levels <5.6%, a statistically significant relationship existed between periodontitis and LBW. Using the Centre for Disease Control/American Academy of Periodontics criteria, the ORadjusted was 1.55; 95% CI: 1.04 to 2.31; using the Gomes‐Filho et al. criteria the ORadjusted was 1.91; 95% CI, 1.06 to 3.45. In the group with higher HbA1c levels but still within the normal range (≥5.6% and <6.5%), the findings showed no association between periodontitis and LBW. Conclusion: Higher maternal glycemic levels within the normal range, inferior to those indicative of gestational diabetes, diabetes mellitus, or hyperglycemia, and periodontitis have opposing effects on BW, altering the association magnitude.